Consumer Protection in Motorcycle Sale and Purchase Transactions on Facebook Marketplace - Nadiarta, I Putu Endrawan Ananda; Arjaya, I Made; Mahaputra, I B GD Agustya (Journal of Tourism Economics and Policy, 2026)
The development of information technology has transformed conventional sale and purchase transactions into electronic-based commerce through digital marketplaces, including Facebook Marketplace. This platform is widely used for motorcycle transactions due to its accessibility and broad market reach. However, the absence of identity verification systems and integrated payment mechanisms increases the risk of fraud causing consumer losses. This study aims to analyze the legal regulation of fraud in motorcycle transactions conducted through Facebook Marketplace and to examine the forms of legal protection provided to consumers. This research employs a normative legal method with statutory, conceptual, and case approaches. The findings indicate that fraudulent acts may be prosecuted under Article 378 of the Indonesian Criminal Code and Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the Electronic Information and Transactions Law. Consumer protection remains predominantly repressive and has not been optimally implemented preventively. Strengthening regulations, enhancing platform responsibility, and increasing public legal awareness are necessary to ensure effective consumer protection.